Oxi hóa chọc lọc ancol benzylic trên xúc tác perovskit chứa crom mang trên oxit mao quản trung bình - Thuận, Ngô Thị; Thảo, Nguyễn Tiến; Thắm, Phạm Thị (Vietnam Journal of Chemistry, 2014)
A perovskite containing-chromium supported on the mesoporous material was synthesized by hydrothermal method using hexadexyl trimethyl ammonium bromide. The solid was characterized by several techniques including X-ray diffraction, SEM, TEM, and Raman spectrocopy. The obtained material has been tested for the liquid oxidation of benzyl alcohol under milder conditions. A rather high selectivity to benzaldehyde is formed.